Enhancing college English writing through self-efficacy-based instruction - Jiang, Huiling (Frontiers in Psychology, 2025)
This quasi-experimental study implemented a 15-week instructional intervention targeting first-year non-English major college students. The intervention integrated differentiated instruction, multi-source feedback, and a structured three-phase writing instruction, emphasizing offering level-appropriate scaffolding, facilitating mastery experiences, and promoting self-regulated learning behaviors. Pre- and post-intervention tests were conducted to examine changes in students’ writing self-efficacy and writing performance. The results indicated significant improvements in both writing confidence and actual writing quality. Key findings are summarized as follows: (1) Students exhibited a significant increase in writing self-efficacy and writing performance, supporting the effectiveness of teaching intervention. (2) A strong positive correlation was observed between writing self-efficacy and writing performance, reinforcing the theoretical proposition that efficacy beliefs positively influence writing engagement and performance. (3) Self-regulated learning behaviors functioned as a critical mediating factor between psychological beliefs and writing performance, highlighting the essential role of agency in the writing process. (4) Differentiated instruction effectively accommodated individual differences in language proficiency and learning needs, enabling learners at all levels to have targeted support and achieve meaningful progress. The study demonstrates that an integrated approach combining psychological development and skill-based training fosters a profound cycle between confidence and competence. This “confidence-skill synergy” model offers a practical and scalable framework for improving English as a Foreign Language writing instruction across diverse classroom contexts.